The Political Dynamics of Space Behind the Jakarta–Bandung High-Speed Rail (Whoosh) Megaproject Development - Mumtaz, Sarah (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
This paper explores the Jakarta–Bandung High-Speed Rail (HSR) megaproject, which began in 2016 and was completed in 2023. Currently, the high-speed train, known as